Core-shell amorphous metal oxides/metallic glassy particles for absorbing application of toxic heavy metal and electromagnetic wave. (15th April 2017) - Wang, DongJun; An, Yongliang; Qiang, JianMing; Yuan, Hao
Abstract: Ti-based metallic glassy powders were utilized as dealloying precursors and core-shell structured absorbents with metallic glassy particles as core and amorphous metal oxides as shell were synthesized through hydrothermal method. The absorbents exhibited superior adsorption efficiency and capacity for removing toxic Cr 6 + in aqueous solution. In addition, the electromagnetic wave absorption properties were investigated and the absorbents had considerable electromagnetic wave absorbing ability owing to its dielectric loss. This work provides a strategy for fabrication of core-shell particles using facile dealloying of multiple component alloys. Graphical abstract: